Dimensi Kearifan Lokal Berbasis Cerita Rakyat sebagai Bahan Ajar Sastra Nusantara dalam Membentuk Karakter Mahasiswa - Eka Alwiah Haseng; Silvin Panca Rina Oktavie (Lembaga Penelitian Mahasiswa Penalaran UNM, 2022)
This study aims to determine the value of local wisdom contained in various folklores that developed in West Sulawesi. In addition, based on the value of local wisdom obtained from folklore, it is hoped that it can strengthen the student's personality. The type of research used is qualitative research with a descriptive approach using data analysis techniques adapted from the flow analysis model. Overall, the total data obtained were 30 (thirty) data containing the content of the Malaqbiq trilogy, including Malaqbiq Pau (malaqbiq in speech) (Honest (jujur)), Malaqbiq Kedo (malaqbiqin attitude) (Toughness (randasa), Perseverance (mattonga-tongan), Lying for the good (alosongan macoa), Courageous (barani), Not prejudiced (pikkiran macoa), Firm (tegas), Compassion (si asayangngi), and Responsibility (peduli)), and Malaqbiq Gauq (malaqbiq in social behavior) (Generous (andang makikkir), Friendly (marawa), Reciprocating (maqbalas jasa), Wise (bijassana), Caring (attention), Right on promise (right on promise), and Helper (pattolong). Based on the classification of moral values in the Malaqbiq Trilogy, overall the moral values contained in the three folklores are selected so that the types of folklore and the values contained can be used as teaching materials for Nusantara Literature in shaping and strengthening the character of students.